2008
DOI: 10.3748/wjg.14.6840
|View full text |Cite
|
Sign up to set email alerts
|

Serum neopterin levels in children with hepatitis-B-related chronic liver disease and its relationship to disease severity

Abstract: AIM:To evaluate serum neopterin levels and their correlations with liver function tests and histological grade in children with hepatitis-B-related chronic liver disease. METHODS: The study population comprised 48 patients with chronic active hepatitis B, 32 patients with hepatitis-B-related active liver cirrhosis and 40 normal controls. Serum neopterin was measured using an enzyme-linked immunosorbent assay. RESULTS: The mean ± SD serum neopterin levels were 14.2 ± 5.6 nmol/L in patients with chronic hepatiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 20 publications
1
10
0
Order By: Relevance
“…It is known to be a marker of inflammation associated with cell-mediated immunity in various diseases (7,14,15,18,20). In our institution, we had observed that patients with a confirmed diagnosis of HLH had very high serum neopterin levels.…”
mentioning
confidence: 66%
See 1 more Smart Citation
“…It is known to be a marker of inflammation associated with cell-mediated immunity in various diseases (7,14,15,18,20). In our institution, we had observed that patients with a confirmed diagnosis of HLH had very high serum neopterin levels.…”
mentioning
confidence: 66%
“…The control group included only JDM patients, which was the only patient group available that routinely had serum neopterin levels measured as an assessment of their disease activity. Elevated serum neopterin levels have been observed with posttraumatic complications among patients with multiple injuries, viral and bacterial infections, and malignancies (3,7,14,15,18,20), and no patients with these complications were included in our study. Therefore, a prospective study should be designed to include other patient populations.…”
Section: Discussionmentioning
confidence: 99%
“…It is known to be a marker of inflammation and associated with cell-mediated immunity in various diseases (Hoffmann et al, 2003) and neopterin changes in peripheral blood may have therapeutic and/or diagnostic value (Fuchs et al, 1993;Cesur, 2005). Significant increases in serum neopterin levels have been reported in many studies (Widner et al, 2002;Hoffmann et al, 2003;Sweeten et al, 2003;Coskun et al, 2005;Cesur, 2005;Pacileo et al, 2007;Gulcan et al, 2008;Celik et al, 2010;Sucher et al, 2010, Matz et al, 2012 (Table 1).…”
Section: Introductionmentioning
confidence: 87%
“…Goris considered neopterin concentration along with other parameters as a tool for inflammation monitoring [16]. High serum levels of neopterin were observed in patients with cirrhosis and also in patients with chronic hepatitis (B and C) [17,18]. Increased serum neopterin levels over 19.15 nmol/l are associated with higher mortality rates in patients with alcoholic liver disease [19].…”
Section: Introductionmentioning
confidence: 99%